Equipment at Ste Madeleine Factory - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Multiple effect evaporators at Ste Madeleine Factory.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar—Manufacture and refining—Equipment and supplies